Tail stump sperm defect as a cause of sterility in an indobrasil (Bus indicus) bull - Rodríguez-Martínez, H. (1998)
The first known case of an Indobrasil (BOA indicus) bull, with a frequency of 100% of the specific sperm abnormality, known as ‘tail stump sperm defect’ is reported. A 5-year old bull was located as a breeding sire in the dry Pacific zone of the tropical Costa Rica, but no pregnancies were diagnosed after 3 months of natural mating with a group of 60 cows. A breeding sound- ness evaluation showed no major clinical abnormalities at the general sire evaluation and the specific examination of his repm- ductive organs, except for bilateral smaller size of the epi- didymal tails. The collection of three consecutive semen samples by electro-ejaculation, showed sperm akinesia in all of the semen samples, together with the presence of the tail stump sperm defect in all spermatozoa. The clinical findings and mor- phological aspects, including light and scanning electron microscopy of the defect, are presented.